2010
DOI: 10.1111/j.1751-7893.2010.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

What makes Early Intervention in Psychosis services effective? A Case Study

Abstract: A number of studies have demonstrated that Early Intervention in Psychosis (EIP) services can produce improved outcomes for service users. However, the essential elements that produce these results remain elusive. This paper considers a number of hypotheses, with a particular focus on one service in the UK, which was designed according to policy guidance. It concludes that the structure of EIP services allows for the effective implementation of evidence based psychosocial interventions, which often fail to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Brabban and Dodgson () argued that the structure of EIP allows for evidence‐based psychosocial interventions (PSI) to be implemented more effectively (than in standard care), and it is this that helps to promote a more successful outcome for service users. The cap on the number of clients on care coordinators’ caseloads in EIP services also affords these opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Brabban and Dodgson () argued that the structure of EIP allows for evidence‐based psychosocial interventions (PSI) to be implemented more effectively (than in standard care), and it is this that helps to promote a more successful outcome for service users. The cap on the number of clients on care coordinators’ caseloads in EIP services also affords these opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…A stand‐alone specialist team with trained staff and small caseloads is advocated as the gold standard to deliver the model, but is not always feasible to implement. Alternative approaches embed EPI delivery within general mental health teams, supported by strategies such as whole team education, training of selected team staff as EPI specialists, providing protocols for identifying and managing first‐episode clients, supervision by EPI specialists, protecting staff time for EPI delivery and establishing area early intervention networks . Studies have shown that alternative models can deliver the complement of services that constitute EPI, with positive results …”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches embed EPI delivery within general mental health teams, supported by strategies such as whole team education, training of selected team staff as EPI specialists, providing protocols for identifying and managing firstepisode clients, supervision by EPI specialists, protecting staff time for EPI delivery and establishing area early intervention networks. [20][21][22][23] Studies have shown that alternative models can deliver the complement of services that constitute EPI, with positive results. [23][24][25] Embedded approaches are often used in rural areas where a central specialist team may be difficult to staff and challenging for clients to access.…”
Section: Introductionmentioning
confidence: 99%
“…This does not necessarily detract from the importance of specialized early intervention programs for psychosis as the potential benefits of such efforts may be more influenced by the content of intervention rather than timing Brabban & Dodgson, 2010 ;Singh, 2010).…”
Section: Discussionmentioning
confidence: 96%